Polydactyly and Single Umbilical Artery: Lesser Known Associations with Beckwith–Weidemann Syndrome - Deepika Rustogi (Indian Pediatrics Case Reports, 2022)
Background: Beckwith–Wiedemann syndrome (BWS) is the most common genetic overgrowth syndrome characterized by the triad of macroglossia, macrosomia, and abdominal wall defects. Clinical Description: We report the case of a term baby girl who was born with mesoaxial polydactyly of her left foot. There were no significant antenatal events or exposure to teratogens, although a single umbilical artery (SUA) had been detected on antenatal ultrasonography. There was no evidence of in utero growth retardation. The birth weight was 3.3 kg and the perinatal transition was uneventful. The general physical and systemic examination was otherwise remarkable. Targeted search for concealed major anomalies was negative and the baby was discharged as nonsyndromic polydactyly, emphasizing the need for regular vigilant surveillance on follow-up. At 6 weeks, significant hypertrophy of the left lower limb was noted. This led the direction of evaluation toward lateralized overgrowth syndromes. Management: The application of the diagnostic algorithm prompted us to order first-tier genetic testing by methylation-specific multiplex ligation-dependent probe amplification assay. This identified aberrant DNA methylation in the chromosome 11p15 region, establishing the diagnosis of BWS. SUA and polydactyly have not been reported in combination in BWS earlier. Conclusions: Neonates with minor anomalies should always have a detailed physical examination at birth and be actively evaluated for major concealed anomalies. Since many clinical manifestations become apparent with age, it is vital that affected babies be kept under close surveillance. A rationale, individualized, step-wise approach with multidisciplinary teamwork helps in establishing the diagnosis in infants with dysmorphic features.